Spinal Tumors: Local Experience - Mahmood, Ashraf; Shehzad, Yasir; Sarwar, Soban (International Journal of Pathology, 2018)
AbstractBackground: Delay in presentation, diagnosis and management contributes significantly in morbidity(Quadriplegic and Paraplegic Injuries) and mortality of patients of Spinal tumours.Objective: To assess the outcome of various modalities and treatment related to prevention of permanentdisability among these patients based on a local experience.Material and methods: 40 patients with spinal tumours who were treated surgically at a tertiary care centreof Rawalpindi Medical College & its allied hospitals from February 2010 to February 2012. Frankel grade scalewas used to categorize and assess the patients before and after treatment.Results: There were 23 males and 17 female patients with an average age of 40 years. 15 of the spinal tumourswere benign, another 15 were primary malignant and remaining 10 were metastatic tumours from various organsof the body including thyroid, prostate, lungs and the ovaries and the unknown primary. Weakness of the limbswas the most common symptoms followed by spasticity and pain. The average duration of systems was 5 monthsMRI was the modality used for the diagnosis of these tumours. Plain radiographs of the spine revealed bonychanges in 50% of the patients. Histopathology revealed that the primary malignant spinal tumours were mostlylymphomas followed by myelomas and sarcomas.Conclusion: Overall neurological improvement occurred in 75% of the patients, 2 patients expired after surgeryalthough the mortality was not directly related to the procedure.